Jaja z porozumienia narodowego [wielkanocna karta okolicznościowa] . National accords are a joke. Easter greeting card - Wolność-Sprawiedliwość-Niepodległość (WSN). (Wolność-Sprawiedliwość-Niepodległość, 1984)
Postcard with b&w print on white paper, with back divided into a note field and an address field. Handwritten note in blue ink. Easter greeting card contains a graphic image which represents three Easter eggs lying on a newspaper. The newspaper symbolizes the official propaganda. The captions on the eggs signify the institutions of the Martial Law: official trade unions, Patriotic Front of National Salvation (Pol. acronym PRON) and Military Council of National Salvation (Pol. acronym WRON). The handwritten note on the back contains greetings from a Theatrology student club, probably to Radio Free Europe. Price: 25 zł.